Реформування освіти як чинник подолання її кризи - Агаларова, Карина Адільївна; Сутула, Оксана Анатоліївна (НТУ "ХПІ", 2018)
Стаття присвячена розгляду реформування освіти як чинник подолання її кризи. У статті підкреслюється, що в подоланні кризи цивілізації, у вирішенні найгостріших глобальних проблем людства величезна роль належить освіті. Аналізується стан сучасної освіти. Обґрунтовуються потреба і причини у проведенні кардинальних змін у вищій освіті України. Зроблено висновок про актуальність проблеми реформування сучасної системи освіти, пошуку нових підходів передачі знань, навичок, нетрадиційних методів навчання, і формування нової парадигми.

The article is devoted to the reform of education as a factor in overcoming its crisis. The article emphasizes that in overcoming the crisis of civilization, in solving the most acute global problems of humanity, a huge role belongs to education. The state of modern education is analyzed. In our country, the crisis of education has a dual nature. First, it is a manifestation of the global educational crisis. Secondly, it occurs under the powerful influence of the crisis of the state, the entire socio-economic and socio-political system. The necessity and reasons for carrying out fundamental changes in higher education of Ukraine are substantiated. It is noted that the crisis of education, which scientists have talked about in recent years, is manifested in the inconsistency of the level of training specialists with the growing needs of society, the demands of a multi-faceted and controversial life, which is increasingly complicated; in the contradiction between the new goals and objectives of higher education and the existing organizational structure, conservative forms of management and operation of higher education; in the differentiation of interests and opportunities of subjects of the educational process. The conclusion is made of the urgency of the problem of reforming the modern educational system, the search for new approaches to the transfer of knowledge, skills, nontraditional learning methods, and the formation of a new paradigm.
Reforming education as a factor in overcoming its crisis
Keywords: криза освіти; зміна парадигм; цілі освіти; вища школа; crisis of education; paradigm shift; educational goals